Ferroelectric polarization promoted bulk charge separation for highly efficient CO2 photoreduction of SrBi4Ti4O15 - Tu, Shu Chen; Zhang, Yihe; Reshak, Ali Hussain; Auluck, Sushil; Ye, Li Qun; Han, Xiao Peng; Ma, Tianyi; Huang, Hongwei (Elsevier, 2019)
Fast recombination of photogenerated charge carriers in bulk remains the major obstacle for photocatalysis nowadays. Developing ferroelectrics directly as photoactive semiconducting catalysts may be promising in view of the strong ferroelectric polarization that induces the anisotropic charge separation. Here, we report a ferroelectric layered perovskite SrBi4Ti4O15 as a robust photocatalyst for efficient CO2 reduction. In the absence of co-catalysts and sacrificial agents, the annealed SrBi4Ti4O15 nanosheets with the strongest ferroelectricity cast a prominent photocatalytic CO2 reduction activity for CH4 evolution with a rate of 19.8 μmol h−1 g−1 in the gas-solid reaction system, achieving an apparent quantum yield (AQY) of 1.33% at 365 nm, outperforming most of the reported photocatalysts. The ferroelectric hysteresis loop, piezoresponse force microscopy (PFM) and ns-level time-resolved fluorescence spectra uncover that the outstanding CO2 photoreduction activity of SrBi4Ti4O15 mainly stems from the strong ferroelectric spontaneous polarization along [100] direction, which allows efficient bulk charge separation along opposite direction. DFT calculations also disclose that both electrons and holes show the smallest effective masses along a axis, verifying the high mobility of charge carriers facilitated by ferroelectric polarization. This study suggests that the traditionally semiconducting ferroelectric materials that have long been studied as ferro/piezoelectric ceramics now may be powerfully applied in the photocatalytic field to deal with the growing energy crisis.